MINI REVIEW ABOUT RISKS OF RADIATION IN MEDICINE - Sattar, Fatema; Amer, Ali Razzaq; Dhay Kazem Jabbar; Raziq, Zahraa Ayed; Mahdi, Shahad yousif (PT. Antis International Publisher, 2024)
Radiation is currently widely used and routinely applied in medicine. Diagnostic radiology, nuclear medicine, and radiation treatment have grown from their primitive beginnings 100 years ago to modern methods that are regarded as critical tools across all fields and specializations of medicine today. Ionizing radiation's inherent qualities give numerous benefits, but they can also be harmful. Its usage in medical practice requires an informed decision on the risk-benefit ratio. This choice requires knowledge of radiation in general as well as medical skill in specific. This review investigated the risks associated with radiation, their connection to medicine, and the advancements in diagnostic and therapeutic technologies. Radioactive substances and radiation are used in medicine, research, and diagnosis. The forms of radiation and their varied impacts on medicine, particularly in the treatment and diagnosis of disorders like cancer, were disclosed by our review's conclusions. It has been demonstrated that mistakes in radiation dosage can result in health issues, hence managing radiation must be done carefully both during research and in practice